Genomic and ecological evidence shed light on the recent demographic history of two related invasive insects - Poveda Martínez, Daniel Alexander (2022)
Hypogeococcus pungens is a species complex native to southern South America that is composed of at least five putative species, each one specialized in the use of different host plants. Two of these undescribed species were registered as invasive in Central and North America: Hyp-C is a cactophagous mealybug that became an important pest that threatens endemic cactus species in Puerto Rico, and Hyp-AP feeds on Amaranthaceae and Portulacaceae hosts, but does not produce severe damage to the host plants. We quantified genomic variation and investigated the demographic history of both invasive species by means of coalescent-based simulations using high throughput sequencing data. We also evaluated the incidence of host plant infestation produced by both species and used an ecological niche modeling approach to assess potential distribution under current and future climatic scenarios. Our genetic survey evinced the footprints of strong effective population size reduction and signals of genetic differentiation among populations within each species. Incidence of plant attacks varied between species and among populations within species, with some host plant species preferred over others. Ecological niche modeling suggested that under future climatic scenarios both species would expand their distribution ranges in Puerto Rico. These results provide valuable information for the design of efficient management and control strategies of the Puerto Rican cactus pest and shed light on the evolutionary pathways of biological invasions.